18F-FDOPA PET/CT Findings in a Patient With Primary Cerebral Amyloidoma. (April 2020) - Rozenblum, Laura; Bertaux, Marc; Bielle, Franck; Ollivier, Morgan; Choquet, Sylvain; Garcilazo, Ytel; Mokhtari, Karima; Kas, Aurélie
Abstract : Abstract: Amino acid PET, including 18 F-FDOPA, is recommended for initial characterization, delineation of tumor extent, and follow-up of gliomas because of its high diagnostic performances. 18 F-FDOPA accumulates inside tumor cells via the L-type amino acid transporter 1 (LAT1) whose expression is increased in gliomas. We report here a case of a histopathologically proven brain amyloidoma that was first addressed for a suspected glioma. Congo red staining showed scattered extracellular deposits of amyloid and immunohistochemistry-highlighted LAT1 expression, explaining the high 18 F-FDOPA uptake found in this lesion. This case indicates that differential diagnosis of the 18 F-FDOPA uptake in brain lesions should include amyloidoma.